2015
DOI: 10.2106/jbjs.n.00488
|View full text |Cite
|
Sign up to set email alerts
|

The Inadequacy of Musculoskeletal Knowledge in Graduating Medical Students in the United Kingdom

Abstract: Our findings suggest that medical schools may be currently failing to ensure that medical students have a basic competence in musculoskeletal medicine. Further investigation is warranted to fully assess the current training provided by U.K. medical schools in musculoskeletal medicine, and appropriate steps must be taken to improve the quantity and quality of training in musculoskeletal medicine in the United Kingdom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 23 publications
3
41
0
Order By: Relevance
“…A number of studies have found that inadequate clinical exposure to MSK medicine during medical school could result in residents and physicians across many specialties who feel underprepared to appropriately evaluate MSK conditions [1,5,6,11,12,15]. For the majority of physicians entering general practice, the primary instruction they receive in the diagnosis and initial management of MSK disorders is during their medical school education [18] because most residents in non-MSK specialties are provided little additional instruction in MSK medicine during their residency training [11,14,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have found that inadequate clinical exposure to MSK medicine during medical school could result in residents and physicians across many specialties who feel underprepared to appropriately evaluate MSK conditions [1,5,6,11,12,15]. For the majority of physicians entering general practice, the primary instruction they receive in the diagnosis and initial management of MSK disorders is during their medical school education [18] because most residents in non-MSK specialties are provided little additional instruction in MSK medicine during their residency training [11,14,20].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies [1,5,9,12,13,17,21] and the American Association of Medical Colleges (AAMC) [3] have raised concern that medical schools may not give sufficient instruction on this topic. In 2003, DiCaprio et al [9] demonstrated the lack of required instruction in MSK medicine in both preclinical and clinical years of undergraduate medical education.…”
Section: Introductionmentioning
confidence: 99%
“…Musculoskeletal pain ranks third as a reason for adolescent medical visits to the primary care physician [5]. In addition, musculoskeletal injuries are one of the most common reason for acute visits to the emergency department and primary care office [1][2][3][4]. Recognition of musculoskeletal diagnoses is very important in a pediatric clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 10% -30% of patients who are seen by a primary care physician are seeking care due to a musculoskeletal complaint [1][2][3][4]. De Inocencio reports that >6% or pediatric clinic visits are musculoskeletal pain with nearly 30% attributable to trauma or overuse 4 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study from the United Kingdom suggested that UK medical schools may be failing to ensure that medical students have acquired a basic competence in musculoskeletal medicine. 31 In fact only 21% of students passed the Freedman and Bernstein musculoskeletal cognitive examination. 32 The situation does not appear to be much better in South Africa, where a similar study (involving interns) found a 91% failure rate.…”
Section: Assessmentmentioning
confidence: 99%